Microstructure of development Al-Mg-Si-Cu powder metallurgy under different addition of Sn - Khairunnisa Omar (Universiti Malaysia Perlis, 2008)
This project involve 3 sample types that had labeled as Premix A (1%Sn addition), Premix B (1.5%Sn addition) and Premix C (2.0%Sn), each types have five samples. After compaction process measured the weight, thickness, width, length, volume, and density. Sintered those samples at 590°C with 5°C/min of heating rate and measure same like during before sintered. Porosity test done by manually measure by weighing samples at three conditions: normal (air), immersed in water and drying after immersed then calculate using formula of porosity. The average result for Premix A is 6% pores, 2.5% pores for Premix B and 3% pores for Premix C. Hardness test had been done by using Macro hardness Vickers. The average result for Premix A is 36.6 HV, 34.8 HV for Premix B and 40.1 HV for Premix C. Finally, observed microstructure using image analyzer with analyzed the grain boundary of microstructure by make samples preparation first. The optimum percent Sn has been determined by compare samples to each test that have done which are conclude by higher hardness and lower % pores. Notice that, Premix C is the optimum values where got 40.1 HV and 3% pores.